Analyze and identify the patient safety culture and possible predictors and areas for improvement related to patient safety culture of Saudi Arabia (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Patient outcomes and the effectiveness of the healthcare system as a whole are substantiallyimpacted by patient safety culture, which is a crucial aspect of healthcare quality. This research analyzesand identifies Saudi Arabia's patient safety culture, along with potential predictors and areas fordevelopment. The present research is an electronic, cross-sectional, descriptive survey of communitypharmacy pharmacists. In accordance with recommendations made by the Agency for HealthcareResearch and Quality (AHRQ), the positive response rate (PRR) was determined. The findings of thepresent research suggest that there is room for improvement in patient safety across a number ofcommunity pharmacies. However, a high response rate must be taken into consideration whileprioritizing the necessity.